Quetiapine induced hair loss in an adolescent case - Yazici, Kemal Utku; Percinel, Ipek (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2015)
Hair loss is a frequently seen side-effect of psychotropic medicaments. Beside the psychotropic medicaments valproic acid and lithium, mostly blamed for alopecia, also cases due to use of antidepressants and typical/atypical antipsychotics have been reported. However, studies on alopecia caused by atypical antipsychotic drugs are scarce and limited by case reports. In this paper, a 16-year-old adolescent female patient developing diffuse alopecia associated with use of quetiapine and recovering after cessation of the medicament is presented. As far as we know, this is the first case reporting quetiapine-associated alopecia in an adolescent.
Bir ergen olguda ketiyapin kullanımına bağlı saç dökülmesi
Keywords: quetiapine; alopecia; side effects; adolescent